2016
DOI: 10.1002/jclp.22435
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Perfectionism and Psychopathology: A Meta‐Analysis

Abstract: Findings support the notion of perfectionism as a transdiagnostic factor by demonstrating that both dimensions are associated with various forms of psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
342
5
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 409 publications
(448 citation statements)
references
References 67 publications
(111 reference statements)
30
342
5
15
Order By: Relevance
“…To our knowledge, no other study has examined the relationship between SOP and depression in youth athletes. However, recent meta-analytical evidence has found SOP to have a small positive correlation with depression that disappeared when controlling for PC or baseline depression in clinical and non-clinical samples (Limburg et al, 2016;Smith et al, 2016). Our findings are consistent with this research.…”
Section: The Relationship Between Perfectionism and Depressionsupporting
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, no other study has examined the relationship between SOP and depression in youth athletes. However, recent meta-analytical evidence has found SOP to have a small positive correlation with depression that disappeared when controlling for PC or baseline depression in clinical and non-clinical samples (Limburg et al, 2016;Smith et al, 2016). Our findings are consistent with this research.…”
Section: The Relationship Between Perfectionism and Depressionsupporting
confidence: 92%
“…However, findings are broadly similar with research outside of sport with dimensions of perfectionism similar to PC positively related to depression in athletes (e.g., Nixdorf et al, 2016). Drawing on the considerable number of studies examining the relationship between perfectionism and depression outside of sport, both PS and PC tend to be positively related to depression, although the size of the relationship is larger and more consistent for PC than PS (see Limburg, Watson, Hagger, & Egan, 2016). Notably, Smith et al (2016) recently conducted a meta-analysis of 10 longitudinal studies and found that both PC and PS displayed a small positive relationship with depression.…”
Section: Relationships Between Perfectionism Burnout and Depressionsupporting
confidence: 77%
“…overevaluation of striving factor was correlated with the evaluative concerns factor of the FMPS (Egan et al, 2016), and that overevaluation of striving was related to eating disorder symptoms (Limburg et al, 2017), because they did not partial out the common clinical perfectionism factor. After the general clinical perfectionism factor is accounted for, remaining variance in these items may reflect more adaptive high standards and deferment of gratification (i.e., missing out on things).…”
Section: Discussionmentioning
confidence: 94%
“…The perfectionistic strivings factor contains items relating to setting high personal standards and goals for achievement, while the perfectionistic concerns factor contains items relating to having a concern over making mistakes and believing that others expect perfection from oneself. Narrative (Bardone-Cone et al, 2007;Egan et al, 2011) and meta-analytic (Limburg et al, 2017) reviews have not found an impact of eating disorder subtype on levels of perfectionism, with no significant differences between individuals with anorexia nervosa and bulimia nervosa in global levels of perfectionism or on perfectionism subscales, such as perfectionistic strivings and perfectionistic concerns. Narrative (Bardone-Cone et al, 2007;Egan et al, 2011) and meta-analytic (Limburg et al, 2017) reviews have not found an impact of eating disorder subtype on levels of perfectionism, with no significant differences between individuals with anorexia nervosa and bulimia nervosa in global levels of perfectionism or on perfectionism subscales, such as perfectionistic strivings and perfectionistic concerns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation